2021
DOI: 10.1021/acs.inorgchem.0c02875
|View full text |Cite
|
Sign up to set email alerts
|

New 3D Porous Silver Nanopolycluster as a Highly Effective Supercapacitor Electrode: Synthesis and Study of the Optical and Electrochemical Properties

Abstract: A high-nucleus silver nanopolycluster as a new type of silver-based polymer supercapacitor (SSc) by a simple and single-step synthesis process was designed and synthesized. The structural, optical, and electrochemical properties of SSc-2 were determined. This highly stable conductive 3D nanopolycluster shows great cycling stability, large capacity, and high energy density without any modification or doping process and so acts as an excellent SSc (412 F g–1 at 1.5 A g–1). In addition, there was a stable cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…26 Since then, many MOF-based electrodes have been reported. 27–57 Very recently, Chen et al synthesized a conductive 3D conjugated copper( ii ) catecholate based MOF (Cu-DBC) and found that it can deliver superior capacitive performances (479 F g −1 at 0.2 A g −1 ). 47 Although much progress has been made in MOF-based electrodes, the used organic linkers are usually costly, seriously restricting their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…26 Since then, many MOF-based electrodes have been reported. 27–57 Very recently, Chen et al synthesized a conductive 3D conjugated copper( ii ) catecholate based MOF (Cu-DBC) and found that it can deliver superior capacitive performances (479 F g −1 at 0.2 A g −1 ). 47 Although much progress has been made in MOF-based electrodes, the used organic linkers are usually costly, seriously restricting their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Their special morphology derived from the threedimensional polymeric structure strongly facilitates electron transfer, which leads to good conductivity. 1 In addition, the synergistic effect of multimetal polyclusters in the role of various active sites could also improve the catalytic performance. 16,17 Interactions such as metallophilic, hydrogen bonding, dipole−dipole, electrostatic, and intermolecular C−H•••π may connect cluster units together in a polycluster.…”
Section: Introductionmentioning
confidence: 99%
“…High-nuclearity clusters, particularly coinage metal clusters with unique sizes and geometrical structures, possess potential applications in fields such as electronics, catalysis, photonics, and biomedicine. Many of these properties depend on their size and structural features. , Gold and silver clusters with optical and electronic properties show significant potential applications in imaging and medical treatment. However, silver clusters show somewhat better optical properties due to the stronger absorption and higher emission quantum yields .…”
Section: Introductionmentioning
confidence: 99%
“…The efficient use of clean energy sources needs to be matched with high-performance energy storage and conversion systems due to solar energy and wind energy being intermittent. , As one kind of important energy storage system, supercapacitors possess the characteristics of a high power density and long cycle stability but lower energy density. To overcome the shortcoming of low energy density and extend the application fields of supercapacitors, various electrode materials have been developed in recent years. Among them, coordination polymers (CPs), especially porous CPs/metal–organic frameworks (MOFs), directly as the electrode materials, have received considerable interest, owing to the porosity and redox-active metal ions/organic ligands in them. Coordination polymers include three kinds of branches, one-dimensional (1D) CPs, two-dimensional (2D) CPs, and three-dimensional (3D) CPs. Many 2D and 3D CP/MOF-based electrode materials for supercapacitors have been reported.…”
Section: Introductionmentioning
confidence: 99%